A Picofarad Capacitance Meter Based on Phase-Sensitive Demodulation for Tomography Application - Alfanz, Rocky; Hamzah, Hamzah; Firmansyah, Teguh; Saraswati, Irma; Ahendyarti, Ceri; Rohmadi, Rohmadi; Muttakin, Imamul (Jurnal Listrik, Instrumentasi, dan Elektronika Terapan, 2023)
Electrical capacitance volume tomography (ECVT) is an imaging technique based on the object’s capacitance value. To provide a representative image of the object under study, the ECVT system requires a method that can measure the capacitance value in the order of picofarads (pF). This level of resolution poses a difficulty for typical commercial capacitance measuring devices, hence raising the need for a specialized method with dedicated signal conditioning circuitry. The capacitance meter based on phase-sensitive demodulation (PSD) is made to solve the aforementioned issue and it is then compared with the characteristics of a capacitance meter-based commercial Arduino setup. The designed PSD-based capacitance measuring device has 97.894% accuracy, precision of 0.704 pF, sensitivity of 0.1197 V/pF, linearity with a coefficient of determination 0.9983, and stability of 0.028 pF/min. In comparison, the capacitance meter based on Arduino has 97.943% accuracy, precision of 0.027 pF, linearity with a coefficient of determination 0.9999, and stability of 0.04 pF/min. Testing is done on an 8-electrode ECVT sensor using dielectric materials of air and water. The nearest electrode pair on the condition of air as the dielectric medium has a capacitance value of 2.62218 pF for PSD-based measuring devices and 3.4027 pF for Arduino-based measuring devices, while the pair of electrodes on the condition of water as a dielectric medium has a capacitance value 9.8229 pF for measuring device based on PSD and 9.1069 pF for Arduino-based measuring devices. The opposite and farthest electrode pair on the condition of air as a dielectric medium has a capacitance value of 0 pF for PSD-based measuring devices and 0,0798pF for Arduino-based measuring devices, while the pair of electrodes on the condition of water as a dielectric medium has a capacitance value of 4.652 pF for PSD-based measuring devices and 0.1224 pF for Arduino-based measuring devices.